NLRP3 Inflammasome and Its Critical Role in Gynecological Disorders and Obstetrical Complications - Fang, Xuhui; Wang, Yanshi; Zhang, Yu; Li, Yelin; Kwak-kim, Joanne; Wu, Li (Frontiers in Immunology, 2021)
Inflammasomes, intracellular, multimeric protein complexes, are assembled when damage signals stimulate nucleotide-binding oligomerization domain receptors (NLRs). Several inflammasomes have been reported, including the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3), NLRP1, NLRP7, ice protease-activating factor (IPAF), absent in melanoma 2 (AIM2) and NLR family CARD domain-containing protein 4 (NLRC4). Among these inflammasomes, the NLRP3 inflammasome is the most well-studied in terms of structure and function. Unlike other inflammasomes that can only be activated by a finite number of pathogenic microorganisms, the NLRP3 inflammasome can be activated by the imbalance of the internal environment and a large number of metabolites. The biochemical function of NLRP3 inflammasome is to activate cysteine-requiring aspartate proteinase-1 (caspase-1), which converts pro-IL-1β and pro-IL-18 into their active forms, namely, IL-1β and IL-18, which are then released into the extracellular space. The well-established, classic role of NLRP3 inflammasome has been implicated in many disorders. In this review, we discuss the current understanding of NLRP3 inflammasome and its critical role in gynecological disorders and obstetrical complications.